Rift Valley fever decision support framework for eastern Africa - Bett, Bernard K. (International Livestock Research Institute, 2015)
In the eastern Africa region, Rift Valley fever (RVF) epidemics occur in irregular cycles that make it difficult for mitigation agents to implement effective interventions in the face of an outbreak. Furthermore, the existing prediction systems do not offer an adequate lead time given that there is inadequate knowledge on drivers and processes that promote outbreaks. The Rift Valley fever (RVF) Decision Support Framework (DSF) has therefore been developed to guide timely, evidenced based decision-making in the control of the disease considering that uncertainties on decision making can paralyse the deployment of effective response measures. The last (2006/2007) outbreak for instance caused substantial socio-economic impacts in the region due to by delays in the recognition of risk and in making decisions to control the disease. The framework breaks the RVF epidemic cycle into five explicit steps and matches them with appropriate actions. These steps identified in the framework include: (i) inter-epidemic period, (ii) pre-outbreak period (classified into early warning, localised rain, flooding and mosquito swarms), (iii) outbreak period (classified into suspected and confirmed outbreak sub-phases), (iv) recovery phase including a 45-day period when no further livestock cases are observed, and (v) post-outbreak recovery and reflection. Interventions matched to these epidemic stages are: capacity building and training, communication, advocacy and public awareness, national and regional coordination, early warning, surveillance, disease prevention, case management, regulation of trade and markets for livestock, resource mobilisation, establishing or strengthening institutions and policies, and risk and impact assessment. The development of the framework has involved multiple partners, decisionmakers to ensure ownership and relevance to the decision-making challenges that have been experienced during previous RVF outbreaks. The framework has also been aligned with the One Health principles by specifying interventions for both veterinary and human health sectors at each decision point. For the framework to be effectively operationalized, three key issues will have to be addressed: (i) a national RVF emergency fund has been established and procedures and modalities put in place to enable the fund to be made available rapidly in response to predetermined criteria, (ii) an effective communication system has been established including a clear chain of command and feedback from the Chief Veterinary/Medical Officers to field officers and communities, and (iii) that approved RVF Contingency Plans integrate the framework in their designs.